Process hazard assessment of energetic ionic liquid with kinetic evaluation and thermal equilibrium. (February 2023) - Yue, Gong; Hong, Su; Liu, Shang-Hao
Abstract: With the continuous development of battery technology, there are new research investments in materials of various parts. In the field of electrolytes, ionic liquids (IL) are considered to be excellent electrolytes and have been widely studied in distinct energy fields. However, it is necessary to pay attention to the safety characteristics of ionic liquids at high temperature due to the application of energy, but there is little research on the reaction and kinetics of ionic liquids. To ensure the safety of ionic liquids, such as high temperature, the common ionic liquid 1-Ethyl-3-methylimidazolium nitrate ([Emim] NO3 ) was selected for analysis. The exothermic mode is obtained from the data of differential scanning calorimetry. The basic reaction parameters of [Emim] NO3 were determined with thermodynamic equation simulation. For ionic liquids in the actual situation, consider adding a heat balance model to estimate its temperature change pattern and find out the hazard temperature and related safety parameters. Temperature changes were estimated by constructing 25.0 g and 50.0 g packages to simulate material reactions and heat transfer in the external environment. The results showed that [Emim] NO3 had shorter TMR ad and TCL (<1 day) when the temperature was above 180 °C. Highlights: Time-saving experimental results are used to verify plant-scale thermal hazards. There are few studies on kinetic analysis of ionic liquids, and analytical models are used for analysis. Advanced reaction order and pre-finger factor can be realized by nonlinear fitting. Heat exchange mode can reflect the influence of external temperature. The key parameters of process safety ( TMR ad and TCL ) can be calculated.